ANALISIS KEBUTUHAN AIR DI SUB DAS KUSAMBI DAS BATULICIN KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Badaruddin Badaruddin (EnviroScienteae, 2017)
The watershed (DAS) is an ecological system in which biotic and abiotic elements interact with each other. Watershed Management is expected to have an economic impact on people living within it without ignoring the sustainability and balance aspects of the watershed ecosystem itself.  This study aims to determine the needs of water in the sub-watershed Kusambi Batulicin watershed. The targeted results will obtain the water balance suitability data based on the water balance, obtain the data of the population residing around the research area, and obtain the land based water management model. The method used to obtain the data is done by descriptive quantitative (primary data and data secondary). From Class Unit land for water availability is determined using runoff coefficient method based on land use information and annual rainfall data. The water requirement is calculated from the conversion to the population's viable living needs. This research uses the approach of the ecological area of Watershed (DAS) which process analysis and presentation is done spatially by utilizing Geographic Information System (GIS) technology.  The result of the research is that the water needs of the people of Tanah Bumbu Regency = (826.352.700/23.340)/365 = 97 liters/person/day, water requirement = (97.229 x 97 x 365)/1.000)/1.000.000 = 3,44 million m3/year. The amount of water required for fisheries in Kusambi sub-waters is 15 liters/second/hectare, and water requirements = ((1,13 x 15 x 24 x 60 x 60 x 180)/1.000)/.1000.000 = 0,53 million m3/year, and the water supply of the Batulicin Watershed Cusambi Sub-watershed with total water needs is still relatively surplus.